The Implication of e-WoM Communication on Customer Preference and Purchase Decision of Electronic Gadgets - Hardjono, Budiono; Riyadi, Sugeng A.; Aris, Diba (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2020)
This study aims to analyze the implications of e-WoM components (intra-personal ties, homophile, credibility) on consumer purchasing decisions both directly and through mediating consumer preferences. Previous experience of consumer purchases conveyed by word of mouth can be a preference for other consumers in buying products or services. The development of digital communication makes electronic Word of Mouth (e-WoM) play an important role in influencing consumer preferences, especially for those who have to make purchasing decisions for products with many features such as gadgets. A total of 300 questionnaires were distributed around Jakarta using simple random sampling and obtained 102 complete responses from respondents. Data analysis was performed using descriptive statistical methods, correlational and multiple regression with the help of SPSS software. The results showed that the gadget purchase decision was partially influenced by consumer purchasing preferences and credibility sources, but this purchase preference was not as dominant as the credibility source. Gadgets are designed unusual and have many advanced technological features compared to conventional products, therefore the results of this study may not be valid for products outside of the gadget. Further research is needed whether e-WoM has the same influence on consumer purchasing decisions of conventional products.